Influence of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty of Shopee on Consumers’ Purchasing Decisions - Andi Supiyandi; Sri Hastjarjo; Yulius Slamet (CommIT (Communication and Information Technology) Journal, 2022)
Shopping through e-commerce is one of the new tools in the current era. Various brands offer the large selection of products or services making shopping through e-commerce like shopping in the city center, but online. Currently, many e-commerce companies are running similar services because e-commerce is important to build a strong brand from the audience and shows the value of the products or services they offer. The aim of the research is to see how significant the influence of Shopee’s brand equity is on consumer purchasing decisions in Indonesia. The research applies a quantitative approach with linear regression analysis to see the causal relationship between variables, with the help of the SPSS 23 application for windows. Data are collected by distributing structured questionnaires online to 100 respondents from various segments of age, gender, and area of residence. The results show that the variables of brand equity including brand awareness, perceived quality, and brand loyalty have an influence on consumer purchasing decisions. However, brand association has no effect on purchasing decision. The most influential variable on purchasing decisions is brand loyalty from all the variables used. Moreover, it is suggested that Shopee application managers should pay more attention to factors that affect brand equity since it has a positive and significant influence on online purchasing decisions.